2020
DOI: 10.1302/0301-620x.102b4.bjj-2018-0991.r3
|View full text |Cite
|
Sign up to set email alerts
|

Increased severity of anaemia is associated with 30-day complications following total joint replacement

Abstract: Aims The aim of this study was to determine the impact of the severity of anaemia on postoperative complications following total hip arthroplasty (THA) and total knee arthroplasty (TKA). Methods A retrospective cohort study was conducted using the American College of Surgeons National Quality Improvement Program (ACS-NSQIP) database. All patients who underwent primary TKA or THA between January 2012 and December 2017 were identified and stratified based upon hematocrit level. In this analysis, we defined anaem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 14 publications
0
36
0
Order By: Relevance
“…These findings are consistent with other studies examining anemia in knee and hip arthroplasty. 10 , 19 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are consistent with other studies examining anemia in knee and hip arthroplasty. 10 , 19 …”
Section: Discussionmentioning
confidence: 99%
“… 3 , 5 , 15 , 17 All primary TSA procedures recorded between 2015 and 2018 were identified using Current Procedure Terminology code 23472. Based on similar categorical values used in other studies, 10 , 14 patients were stratified into 1 of 3 cohorts depending on their preoperative hematocrit (HCT) levels. Patients with greater than 38% preoperative HCT were classified as having normal HCT levels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies performed on THA patients, 52 , 53 and on combined arthroplasty patients, 54 have demonstrated increased odds of postoperative complications, mortality, and surgical site infection in patients with preoperative anaemia. While our study similarly found increased odds of readmission in the TKA population with low HCT, these results were not seen in the THA cohort after adjustment for relevant covariates.…”
Section: Discussionmentioning
confidence: 93%
“…By comparison, PMSA was usually difficult to resolve, needing further treatments, such as intravenous iron, erythropoietin, even transfusion [ 17 , 18 ]. Moreover, patients who developed PMSA had higher risk of developing postoperative complications relative to patients with mild anemia following joint replacement [ 19 ]. Thus, we selected PMSA as the outcome variable, evaluating related risk factor and attempting to decrease the rate.…”
Section: Discussionmentioning
confidence: 99%